ARTISIPASI MASYARAKAT SUB URBAN DALAM PEMBANGUNAN KOTA MALANG - Baroh, Istis (Jurnal Gamma, 2009)
The involvement of financial institutions is needed in the development of its business. What isthe mechanism between home industry partnerships with financial institutions is something thatneeds to be studied so that the synergy between the home industry with a financial institution canrun.This study is proposed as a whole is completed in 2 stages. Phase I aims to: Describe theprofile of home industry & financial institutions in the research area, describe the performance of anexisting home industry in the research area. Phase II aims to: analyze the ever growing system ofcooperation between the home industry with financial institutions in the research area, formulatethe concept of cooperation in order to knit synergy between the home industry with financialinstitutions in order to be profitable for both parties.